Summerland [videorecording (DVD)] - Swale, Jessica; Swale, Jessica; Arterton, Gemma; Mbatha-Raw, Gugu, 1983-; Wilton, Penelope, 1946- (MPI Home Video, 2020)
When a reclusive writer living in southern England during World War II agrees to take in an evacuee from London, she finds herself opening her heart to him.